Graffiti : arte de rua e espaço escolar - Chico, Alana Cristina Teixeira (2017)
This research has as main objective to identify the sociocultural and educational developments that graffiti brings with it, reflecting on the relationship between the graffiti artist and society and on the possibility of working this art as an educational and emancipatory experience within the school environment. For this, we seek to analyze the practices of graffiti inserted in concrete of the city, through historical, social and educational approaches. In addition, we have a rich material of interviews with four Cuiabanos graffiti artists and four students who experienced graffiti art inside the school as a pedagogical activity. Given this, we adopted Action Research as a methodology, since the researcher in question is inserted in the context as a street artist and educator, collectively investigating urban graffiti and educational experiences worked within the school. Moreover, we use Michel Foucault and Michel de Certeau as a theoretical contribution to develop a philosophical reflection of the daily relations and the aesthetic discourses produced by graffiti artists, in which we analyze the syndical representations of the material and nonverbal statements of the graffiti on the walls of the city. And finally, we use Paulo Freire in dialogue with Marilena Chauí, Maria da Glória Gohn and Renato Ortiz, to investigate in which perspectives graffiti can be understood as a pedagogical reference in the school environment and to what extent it can be inserted in the thinking of A dialogical popular education. Regarding the research contributions, it is possible to verify that graffiti has a pedagogical-philosophical nature in which it connects with the popular dimension of communication and escapes from the massification of pedagogical contents and the dominant discourses linked to the media. Finally, we could also verify its character of resistance, emancipation and dialogue in a context of street culture.